BILL 3176/2019, BEHAVIORAL ECONOMICS AND THE OPT-OUT SYSTEM - Morato de Andrade, Otávio (Journal from the Judiciary Section of Rio de Janeiro; Vol 24 No 50 (2020): Saberes em perspectivaDO - 10.30749/2177-8337.v24n50p29-46, 2021)
In recent decades, advances in science have increased the success of transplantation techniques. However, the availability of organs and tissues has not kept pace with the increase in medical needs, generating a dramatic public health situation, where thousands of people die waiting for a transplant. Behavioral Economics, which studies rational limitations in human decision-making, offers solutions to increase organ donation, one of the main ones being presumed consent (also called opt-out). Studies comparing opt-out and opt-in approaches suggest higher rates of donation in countries that adopt the first strategy. It is concluded that, in Brazil, the bill 3.176/2019 can be an opportunity to reduce the organ deficit for transplants, as it aims to implement the behavioral insight of the opt-out, establishing presumed consent for all citizens.